The effect of an educational curriculum using Snokel swimming for new learners aged (8-10) years - Ghazwan, Shams; Mahmoud , Ishraq; Ali , Yasar (Journal of Physical Education, 2025)
The research aimed to design an educational curriculum using the Snokel device in learning freestyle swimming for learners aged (8-10) years, and to identify the effect of an educational curriculum using the Snokel device in learning freestyle swimming for learners aged (8-10) years. The researcher chose the experimental curriculum in the style of two equal groups (experimental and control), with a pre- and post-test. The researcher selected learners in the specialized school affiliated with the Central Iraqi Aquatics Federation aged (8-10) years. Randomly from the research population, which numbered (23) learners, (3) learners were excluded for the exploratory experiment, so that the sample number became (20). After that, the researcher randomly divided the sample into two equal experimental and control groups, each group consisting of (10) learners. The educational units were prepared using the Snokel device in learning free swimming. After completing the duration of applying the educational units, the researcher reached several conclusions, which are: An educational curriculum using the Snokel device affected the tests for free swimming (for the experimental group), and the effect of the prepared curriculum. by the coach in the freestyle swimming tests (for the control group), and the preference for an educational curriculum using the Snokel device prepared by the researcher over the curriculum prepared by the coach in the freestyle swimming tests